Uncovering the Anticancer Mechanisms of Chinese Herbal Medicine Formulas: Therapeutic Alternatives for Liver Cancer - Chen, Feiyu; Zhong, Zhangfeng; Tan, Hor Yue; Guo, Wei; Zhang, Cheng; Tan, Chi-wing; Li, Sha; Wang, Ning; Feng, Yibin (Frontiers in Pharmacology, 2020)
The potential values of Chinese herbal formulas in treating various diseases are well known. In addition to more than 2,000 years of history, herbal medicine is appreciated for its remarkable efficacy in a lot of cases, which warrants a role in public health care worldwide, especially in East Asian countries. Liver cancer is the second most fatal cancer across the world. Recent studies have extensively investigated the chemical profiles and pharmacological effects of Chinese herbal medicine formulas on liver cancer. Either through observational follow-up or experimental studies, multiple herbal formulas have benefits implicated in the management of liver cancer. However, complex composition of each formula imposes restrictions on promoting clinical practice and global recognition. Therefore, understanding the mode of action of Chinese herbal medicine formulas in depth may offer sufficient evidence for their clinical use. This review highlighted the chemical characteristics and molecular mechanisms of actions of prominent Chinese herbal medicine formulas and summarized the correlated findings on the potential use in liver cancer treatment. At last, the present progresses of Chinese herbal medicine formulas in the perspective of clinical trials are discussed.